Challenges of Cerebral Perfusion Pressure Measurement. Issue 6 (December 2017) - Livesay, Sarah L.; McNett, Molly M.; Keller, Monica; Olson, DaiWai M.
Abstract : ABSTRACT: Monitoring cerebral perfusion pressure (CPP) is recommended by a number of clinical practice guidelines and is a routine function performed by critical care neuroscience nurses. However, several studies highlight theoretical and practice variations in the measurement of CPP regarding the location of the arterial pressure transducer during measurement. Agreement on the technique and process for obtaining valid measurements is lacking. This article identifies the challenges associated with CPP measurement and highlights opportunities for standardizing CPP measurement to improve consistency in care and findings reported in the research literature. The challenges associated with practice variations impact multiple nursing domains, including the environment, patient treatment, and team communication; all ultimately impacting nursing workflow. The practice variation and impact on nursing workflow have significant implications for further research, electronic health record development, and refining monitoring technology.